2009
DOI: 10.1111/j.1365-2885.2008.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple oral dosing of valacyclovir in horses and ponies

Abstract: The aim of the current study was to investigate whether multiple oral dosing of valacyclovir could result in plasma concentrations exceeding the EC(50)-value of acyclovir against equine herpesvirus 1 (EHV1) during the majority of the treatment period. Additionally, we wanted to determine the concentration of acyclovir in nasal mucus and cerebrospinal fluid (CSF). Valacyclovir was administered to four horses and two ponies, three times daily, at a dosage of 40 mg/kg, for four consecutive days. Blood was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…2008, 2009). In one study, low concentrations of acyclovir could be detected in nasal mucus samples (mean 0.72 µg/ml; range 0.36–1.17 µg/ml) as well as cerebrospinal fluid samples (mean 0.16 µg/ml; range 0.11–0.23 µg/ml) (Garre et al. 2008).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 84%
See 2 more Smart Citations
“…2008, 2009). In one study, low concentrations of acyclovir could be detected in nasal mucus samples (mean 0.72 µg/ml; range 0.36–1.17 µg/ml) as well as cerebrospinal fluid samples (mean 0.16 µg/ml; range 0.11–0.23 µg/ml) (Garre et al. 2008).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 84%
“…2008). This suggests that there may not be an effective concentration of acyclovir in these tissues that would affect viral replication and shedding and is supported by one in vivo study (Garre et al. 2008).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 84%
See 1 more Smart Citation
“…Valacyclovir, an esterified version of acyclovir, is rapidly converted to acyclovir after absorption and has greater oral bioavailability than acyclovir (Garre et al. , 2008).…”
Section: Pharmacokinetic Parameters (Mean ± Sd) Of Acyclovir In the Pmentioning
confidence: 99%
“…In a previous study, a stallion and some mares with ECE responded well to application of acyclovir, and an inhibitory effect of acyclovir on EHV-3 was shown by plaque reduction assays [6]. Some researchers have used valacyclovir, a prodrug of acyclovir, for treatment of EHV-1 infection, but not for treatment of EHV-3 infection [8,9,10, 15]. Some studies showed that valacyclovir maintained an effective serum concentration for a longer time than did acyclovir [9, 10, 15].…”
mentioning
confidence: 99%